Evaluation of The Relationship Between Frailty and Sleep Quality of Older Adults Living in Nursing Home - Pınar ERMAN; Güler BALCI ALPARSLAN (Yaşlı Sorunları Araştırma Dergisi)
Aim: The aim of this study was to evaluate the relationship between frailty level and sleep quality in elderly people living in Kocaeli Nursing Home. Method: This study is cross-sectional and was conducted with 75 of approximately 90 elderly individuals staying in Kocaeli Nursing Home between 1 March 2022 and 1 September 2022 in the living room, which was open to everyone, at the time of the day when the elderly were available. Results: The mean age of the participants was 76.60∓8.04, 52% were male, 50.7% were married, 41.3% were primary school graduates. It was observed that 45.3% of the participants felt very old, 53.3% were severely frail, and the frailty score of women (mean=11.55) was higher than that of men (mean=8.53) (p=0.001), the mean Edmonton Frailty Scale score of those who perceived themselves as very old (mean=12.38) was higher than those who perceived themselves as old (mean=8.69) and middle-aged (mean=6.46) (p=0.001). 100% of the participants had poor sleep quality. It was found that the mean Pittsburg Sleep Quality Index score of those with chronic disease (mean=13.28) was higher than the mean score of those without chronic disease (mean=11.5) (p=0.001), the mean sleep quality score of those who slept an average of 3-4 hours a day was (mean=10.70), and the mean score of those who slept an average of 4-6 hours a day was (mean=10.13) (p=0.004). Conclusion: When the relationship between Pittsburg Sleep Quality Index and Edmonton Frailty Scale was analysed, no significant relationship was found between them (p=0.797>0.05).